Flexural strength of fiber reinforced posts after mechanical aging by simulated chewing forces. (January 2018) - Irmak, Özgür; Yaman, Batu Can; Lee, Dong Yong; Orhan, Ekim Onur; Mante, Francis K.; Ozer, Fusun
Abstract: This study evaluated the effect of simulated chewing forces on the flexural strength of fiber reinforced posts (FRPs). Four different brands of FRPs were selected as main group for the study: RelyX Fiber Post (RX), IceLight (ICE), Unicore Posts (UC), FlouroPost (FP). Ten posts in each main group didn't receive any aging process and tested as baseline (BL), other ten posts were subjected to simulated chewing forces/mechanical aging (MA) as follows: Post spaces were prepared in acrylic with drill. Depth of preparation was adjusted to leave 4-mm coronal part of posts protruding from canals. Coronal parts were incrementally restored with resin-composite (Clearfil Majesty Posterior A2, Kuraray, Osaka, Japan). Prepared samples were subjected to chewing cycles in a chewing simulator (Chewing Simulator CS-4, Mechatronik, Germany). Flexural strengths of all groups were measured with three-point bending test. Data were analyzed by two-way ANOVA and Tukey's test (α = 0.05). After MA, flexural strengths of all posts were significantly decreased when compared with BL for all FRPs tested (p < 0.05). At BL, highest flexural strength values were obtained for ICE. After MA, similar to BL, highest flexural strength values were obtained for ICE. Only RX showed statistically significant difference when compared with ICE (p < 0.05). UC and FP showed similar flexural strength values with ICE (p > 0.05). It may be concluded that chewing forces on post-core systems may reduce the flexural strengths of FRPs. Highlights: Worst-case scenario where there is no cement between post and root was simulated. Chewing forces reduce the flexural strength of fiber reinforced posts. Mechanical properties seem to be material dependent.